Exploring Undergraduate Students' Experiences with Asynchronous Learning in English for Academic Purpose - Faisal Rahman; Faida Azhimia; Rizky Hidayatullah (JELITA, 2024)
The aim of this research is to identify higher education students’ experience regarding the application of Asynchronous Learning in learning English for Academic Purposes (EAP) so that future improvements can be made. This research method is an analytical survey with an exploratory method and a quantitative approach. The population of this study was 94 students taking EAP course, then 50 people were selected as samples using Simple Random Sampling. The instrument used in this research was questionnaire with 5-point likert scale to gain the data related to students’ experience in the implementation of AL in EAP course. The research results show that students believe that Asynchronous Learning can improve some students learning autonomy, and learning abilities. It is also found that AL can be developed better to help students improve their critical thinking skills, communication skills, social interaction and collaboration between students. Apart from that, students also consider the application of Asynchronous Learning in learning to be enjoyable.